Effects of Al and Ti on thermal expansion behavior of a Ni–Fe–Cr-based superalloy: A combined experimental and first-principle study - Sihan Cheng; Xuezhi Qin; Bin Wen; Jiaqi Wang; Yunsheng Wu; Lanzhang Zhou (Journal of Materials Research and Technology, 2024)
The effects of Al and Ti on the thermal expansion coefficient (TEC) of a Ni–Fe–Cr-based superalloy, for the application of advanced ultra-supercritical (A-USC) systems, were investigated by combining the experiments and first-principles calculations. The results imply that MC/M23C6 carbides and grain boundary seem to play a minor role in the TEC of alloys due to their relatively low proportions. Al and Ti elements increase the TEC of alloys when present in γ matrix, but they decrease the TEC value by taking part in the formation of γ′ phase. When the amount of γ′ phase is low, the TEC of alloys at 600–700 °C is dominated by γ matrix, and consequently shows an increasing or constant trend with the increase of Al + Ti content. Replacing Al element with Ti element decreases the TEC of alloys in two ways: directly by reducing the TECs of γ matrix and γ′ phase, and indirectly by increasing the amount of γ′ phase. These results can provide the theoretical basis and beneficial guidelines for the composition design and optimization of low-expansion superalloys.